Ryzyko i ochrona w środowisku rówieśniczym. Czyli o znaczeniu relacji koleżeńskich w życiu nastolatków - Jankowiak, Barbara; Matysiak-Błaszczyk , Agata (Studia Edukacyjne, 2019)
This article is devoted to the issue of peer relations, which are an important developmental factor and affect the welfare of adolescent boys and girls. According to many authors, relationships with peers during adolescence carry not only risk as a consequence of peer pressure to undertake unfavourable behaviors, but may also potentially contribute to well-being and life success. The analysis of available research results helped to distinguish two main risk factors resulting from peer relations, which include: mutual influence and modelling of disadaptive behaviours and rejection by peers. The protective factors, in turn, included: mutual influence and modelling of adaptive behaviours, a sense of happiness resulting from peer relations and compensating for other difficulties through peer relations.